Konstruksi dan Ornamen pada Alat Musik Tradisional Calong di Sulawesi Barat : Kajian Estetika dan Simbolisme - Ariena Millatie; Salwa Amanda Syakib; Fadyah Nurfadriza; Salwa Al Qorni; Pratama Ilham Abduh Putra; Syairul Bahar; Farkhan Abdurochim Alfarauq (Jurnal Pendidikan Dirgantara, 2025)
The Calong traditional musical instrument from West Sulawesi is a cultural heritage of the Mandar people, possessing strong artistic and symbolic value. However, documentation of the instrument's construction and ornamentation remains limited. This study aims to identify the Calong's construction, analyze the variety of ornaments used, and uncover the aesthetic meaning and symbolism inherent in the instrument. The research method used was descriptive qualitative, with data collection techniques including direct observation, documentation, interviews with craftsmen and artists, and a visit to the West Sulawesi Pavilion at the TMII (Indonesian Museum of Traditional Art) as a comparative source for cultural representation. The results indicate that the Calong's construction utilizes specific bamboo selection and splitting techniques, which influence its resonance quality. The ornamentation reflects symbols of the relationship between humans and nature, ancestors, and the Mandar people's philosophy of life. Aesthetically, the combination of form, texture, and motifs creates a distinctive visual character while strengthening its musical identity. The study's conclusions confirm that the Calong is not only a musical instrument but also a cultural artifact with aesthetic and symbolic value that is important to preserve through education, cultural awareness, and ongoing documentation.